2017
DOI: 10.1590/s1806-37562016000000170
|View full text |Cite
|
Sign up to set email alerts
|

Effects that passive cycling exercise have on muscle strength, duration of mechanical ventilation, and length of hospital stay in critically ill patients: a randomized clinical trial

Abstract: Objective: To evaluate the effects that passive cycling exercise, in combination with conventional physical therapy, have on peripheral muscle strength, duration of mechanical ventilation, and length of hospital stay in critically ill patients admitted to the ICU of a tertiary care university hospital. Methods: This was a randomized clinical trial involving 38 patients (≥ 18 years of age) on mechanical ventilation who were randomly divided into two groups: control (n = 16), receiving conventional physical ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
64
0
12

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(79 citation statements)
references
References 33 publications
3
64
0
12
Order By: Relevance
“…The mean age of the included patients ranged from 44.9 to 65.5 years. Eighteen studies reported Acute Physiology and Chronic Health Evaluation (APACHE) II scores; the mean APACHE II scores ranged from 15.5 to 27.5 points [26,28,29,31,3335,3747]. One study reported a Simplified Acute Physiology Score II [30].…”
Section: Resultsmentioning
confidence: 99%
“…The mean age of the included patients ranged from 44.9 to 65.5 years. Eighteen studies reported Acute Physiology and Chronic Health Evaluation (APACHE) II scores; the mean APACHE II scores ranged from 15.5 to 27.5 points [26,28,29,31,3335,3747]. One study reported a Simplified Acute Physiology Score II [30].…”
Section: Resultsmentioning
confidence: 99%
“…In an RCT of 21 patients with sepsis, those who received short-term early cycling demonstrated preserved muscle fibre cross-sectional area at 7 days 11. In a 49-patient RCT, those who started passive cycling 3 days after ICU admission had larger improvements in strength scores at ICU discharge 12. However, in a recent RCT of 314 patients that added both in-bed cycling and neuromuscular electrical stimulation to early mobilisation in critically ill patients did not improve muscle strength at ICU discharge 13.…”
Section: Introductionmentioning
confidence: 98%
“…Although early active mobilization is associated with improvements in peripheral strength at hospital discharge (3,4) and shorter delirium duration (5), many patients are unable to participate in active mobilization during earlier stages of critical illness due to decreased levels of consciousness and ventilator dependence. In these patients, passive exercise has been reported as a safe and feasible method to incorporate mobilization early in the course of their ICU stay (6), and it is also associated with improved patient motivation during recovery following critical illness (7). However, prior studies that assess the safety and feasibility of early mobilization protocols in critically ill patients primarily do so by confirming the stability of global hemodynamic variables and minimal occurrences of adverse events (3,8).…”
Section: Introductionmentioning
confidence: 99%